2013
DOI: 10.1093/cid/cit129
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interferon γ Detection for the Diagnosis of Previous Q Fever

Abstract: Specific IFN-γ detection is a novel diagnostic assay for previous C. burnetii infection and shows similar performance and practical advantages over serology and ST. Future studies to investigate the clinical value in practice are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 27 publications
2
53
0
Order By: Relevance
“…Previously, our group showed that antigen-specific IFNγ production was significantly higher in QFS patients ( n  = 28; 319.4 pg/mL) than in Q fever seropositive controls ( n  = 135; 120 pg/mL) [8]. It was also shown that antigen-specific IFNγ production is a useful tool for diagnosing a previous Q fever infection [13], and adding antigen-specific IL-2 production helped discriminate chronic Q fever patients from Q fever seropositive controls and QFS patients [8, 17]. In this study, antigen-specific IFNγ production was not significantly higher in QFS patients than in asymptomatic Q fever seropositive controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our group showed that antigen-specific IFNγ production was significantly higher in QFS patients ( n  = 28; 319.4 pg/mL) than in Q fever seropositive controls ( n  = 135; 120 pg/mL) [8]. It was also shown that antigen-specific IFNγ production is a useful tool for diagnosing a previous Q fever infection [13], and adding antigen-specific IL-2 production helped discriminate chronic Q fever patients from Q fever seropositive controls and QFS patients [8, 17]. In this study, antigen-specific IFNγ production was not significantly higher in QFS patients than in asymptomatic Q fever seropositive controls.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against C. burnetii (IgG against phase 1 and phase 2) were measured in 1:32 serum dilution, as described [21]. If positive, exact IgG and IgM titres were determined.…”
Section: Serologymentioning
confidence: 99%
“…In vitro IFN-␥ production after C. burnetii stimulation, measured in a whole-blood assay [21], was expressed as continuous variable with cut-off at 32 pg/mL, based on previous findings [21]. Outcome did not affect the decision to vaccinate.…”
Section: Burnetii Ifn-production-assaymentioning
confidence: 99%
See 2 more Smart Citations